Causal Effect from State Welfare Card on Poverty in Thailand - Phattarasukkumjorn, Weerawat; Suwanmanee, Petnaree (Thailand and The World Economy, 2025)
This study aims to explore whether there is evidence supporting that the State Welfare Card causes the reduction of the poverty rate in Thailand. With data limitations, we rely on the 2019 household socio-economic survey to compare the consumption expenditure of those who received the card (treatment) and those who did not (control) using matching methods with propensity score and coarsened exact matching. The results show that the consumption expenditure of the treatment group is less than that of the control group, which aligns with previous research. We then perform matching among the poor and the non-poor separately and find that among the poor, differences in consumption expenditure between the treatment and control are tiny and mostly not statistically significant. We conclude that there is no sufficient evidence to support the claim that this program causally reduces the number of the poor in Thailand, probably due to the size of the provided benefits that is too small.